Low ALT levels are associated with poor outcomes in acute coronary syndrome patients admitted to the intensive cardiac care unit. (14th October 2021) - Segev, A; Itelmad, E; Beigel, R; Segal, G; Chernomordik, F; Matezky, S; Grupper, A
Abstract: Background: Frailty is an under recognized and important entity that bears worse prognosis. Purpose: Although low serum alanine aminotransferase (ALT) can serve as a novel marker of frailty, its use was never assessed in acute coronary syndrome (ACS) patients. Methods: A retrospective analysis of hospitalized ACS patients in the intensive cardiac care unit (ICCU) between 1/5/2011 and 1/12/2020 at a single tertiary medical center. Results: The study included 3956 patients after excluding patients with ALT >40 IU/L, cirrhosis and missing data, followed for a median duration of 47 months (IQR 20–77). Patients were stratified into two groups based on their first ALT measurement within the index hospitalization: low-normal ALT group (ALT ≤10 IU/L) vs. high-normal ALT group (ALT >10 IU/L). Patients with ALT≤10 IU/L were older (mean age 71 vs. 65, P<0.001), presented more frequently with non-ST elevation myocardial infarction (66.4% vs. 53.2%, P<0.001), had higher rates of comorbidities at baseline, and had a lower Norton score upon admission. Hospitalization length was longer in the low-normal ALT group (P<0.001). Although the in-hospital mortality rate was similar between the groups (0.9% vs. 0.7%, P=0.99), long-term mortality was significantly higher in the low-normal ALT group (22.7% vs. 7.9%, P<0.001). In a multivariate regression model ALT ≤10 IU/l was associated with increased mortality (HR 2.1, 95% CI 1.46–3). Conclusion: Lower serum ALT is associated with worse outcomes in ACS patients admitted to the ICCU. FUNDunding Acknowledgement: Type of funding sources: None.